2020
DOI: 10.1186/s12875-020-01255-1
|View full text |Cite
|
Sign up to set email alerts
|

Professional roles of general practitioners, community pharmacists and specialist providers in collaborative medication deprescribing - a qualitative study

Abstract: Background: Collaborative care approaches between general practitioners (GPs) and pharmacists have received international recognition for medication optimization and deprescribing efforts. Although specialist providers have been shown to influence deprescribing, their profession so far remains omitted from collaborative care approaches for medication optimization. Similarly, while explorative studies on role perception and collaboration between GPs and pharmacists grow, interaction with specialists for medicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
(85 reference statements)
2
20
0
Order By: Relevance
“…In other diseases, models of collaboration in primary care are being developed [ 25 ]. Several studies have showed the recognition of pharmacist and GP roles in collaborative care approaches [ 26 , 27 ]. Once the barriers between pharmacists and GPs were addressed, collaborations were linked to improved patient outcomes [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other diseases, models of collaboration in primary care are being developed [ 25 ]. Several studies have showed the recognition of pharmacist and GP roles in collaborative care approaches [ 26 , 27 ]. Once the barriers between pharmacists and GPs were addressed, collaborations were linked to improved patient outcomes [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of an increasing burden on primary healthcare services, effective multidisciplinary collaboration is crucial for sustaining high quality care [ 23 ]. Nevertheless, interaction with specialists for therapeutic optimisation should not be neglected in order to obtain a transparent continuity of care [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For item development, both deductive and inductive methods were used [ 16 ]. An extensive literature examination was performed, including qualitative design studies, commentaries, letters to the editors, expert opinions, and systematic reviews on the topic, in order to identify key concepts, themes, and factors [ 9 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Authors identified three frequently appearing themes: patient, profession, and organisation.…”
Section: Methodsmentioning
confidence: 99%
“…Clinician barriers also include managing alternate goals during the patient encounter (e.g., achieving glycemic goals to meet a metric or guideline), challenges communicating with other clinical team members, inadequate time and training on how to approach deprescribing, and a lack of clear evidence-based guidelines 85,86 . Conflicts between the role of the pharmacist, primary care physician, and specialists may also impair deprescribing ---and this may be especially challenging if there is not an interoperable electronic health record (EHR) for communicating questions or concerns regarding medications 81,85 .…”
Section: Challenges Of Deprescribingmentioning
confidence: 99%